Pengaruh Habitual Social Media Use Terhadap Kelalaian Ibadah Salat pada Mahasiswa Perguruan Tinggi Berbasis Islam di Banda Aceh - Zahri, Syakira Alfi; Taufik; Anita (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This research was conducted to analyze the influence of habitual social media use on the neglect of prayer obligations among students at Islamic-based universities in Banda Aceh. The phenomenon of automation in social media use has the potential to disrupt students' religious priorities. This study employs a quantitative approach with a survey method involving 107 respondents, obtained through non-probability sampling techniques. Data were analyzed using simple linear regression with the assistance of IBM SPSS 26. There is a significant positive relationship between habitual social media use and the neglect of prayer, as evidenced by a t-value of 6.646, which is greater than the t-table value of 1.982, with a significance of 0.000. The resulting regression equation is Y = 3.096 + 0.641X, where the constant value of 3.096 indicates the baseline level of neglect, while the regression coefficient of 0.641 confirms that every increase in habitual social media use will increase the neglect of prayer. The R-Square contribution of the social media habit variable reaches 29.6%, while the remaining 70.4% is influenced by other internal and external factors outside of this study. This research proves Robert LaRose's theory regarding deficient self-regulation, which shows that uncontrolled social media habits can weaken students' self-regulation in carrying out their prayer obligations.